SUN-912 The Rare Men of Mississippi Complications in the Diagnosis of Multiple Endocrine Neoplasia Type 1 - Rashid, Hytham (J Endocr Soc, 2020)
Background: Multiple endocrine neoplasia type 1 (MEN1) is a rare, autosomal dominant disorder associated with tumors of the parathyroid glands, pituitary gland, and gastroenteropancreatic cells caused by mutations of the MEN1 tumor-suppressor gene. Thescarcity with which this syndrome is encountered makes diagnosis challenging in rural settings. Clinical Case: A 34-year-old male presented to the Emergency Department complaining ofintermittent abdominal pain for the past year, that was associated with nausea, vomiting, and diarrhea. Past medical history was significant for hyperparathyroidism treated with parathyroidectomy, nephrolithiasis, and alcohol-induced chronic pancreatitis. Initial laboratory studies revealed elevated corrected calcium (11.5 mg/dL, n:7.6-10.6 mg/dL) with a subsequent elevated parathyroid hormone level (105, n:14-72 pg/mL). CT scan of the abdomen and pelvis revealed fatty liver changes, nonobstructive nephrolithiasis and pancreatic calcifications. Due to his recurrent symptoms, gastroenterology was consulted for esophagogastroduodenoscopy that revealed erosive esophagitis with multiple duodenal ulcers. The patient was started on a high dose Proton Pump Inhibitor IV and treated supportively. His symptoms improved within a few days. Additional studies were obtained including a gastrin level and H. pylori antigen testing that required sending out to an outside laboratory for analysis. He was discharged with close outpatient follow up scheduled, but then was readmitted two days later with recurrent symptoms. The patient was again treated with supportive care, and was able to provide additional family history revealing parathyroid and ulcer disease in both his father and paternal grandmother, which triggered suspicion for multiple endocrine neoplasia type 1. His gastrin level returned, and was found to be elevated (489 pg/mL, n < 100) with a negative H. pylori antigen, supporting the diagnosis of MEN1. Further diagnostic testing was performed, revealing an elevated serum chromogranin A level (117 ng/mL, n < 15) and abnormalities on MEN1 genetic testing. An Octreotide scan was then performed, showing a single intense area of uptake near the caudate lobe of liver. At this time, he was transferred to a tertiary medical center for further evaluation and management. Conclusion: This case illustrates the significance of suspicion for multiple endocrine neoplasia and the value of a complete history. Additionally, while a serum chromogranin A level can be nonspecific, it can be obtained in an outpatient setting to help differentiate neuroendocrine pathology from other etiologies. Though the symptoms of MEN1 patients can mimic many other disease processes, recognition of symptoms is critical for medical communities to provide swift treatment.